Galileo's glassworks : the telescope and the mirror - Reeves, Eileen Adair (Harvard University Press, 2008)
Galileo and the Dutch telescope have long enjoyed a durable connection in the popular mind, transforming a rather modest middle-aged scholar into the icon of the Copernican Revolution. And yet the speed with which the telescope changed the course of Galileo's life and early modern astronomy obscures his actual delayed encounter with the instrument. This book considers the lapse between the telescope's 1608 creation in The Hague and Galileo's acquaintance with such news ten months later. Along the way, Reeves offers a revised chronology of Galileo's life in this critical period.